KAJIAN TENTANG PENGENALAN KARAKTER MENGGUNAKAN SCALE-INVARIANT FEATURE TRANSFORM - Willian Willian; Lina Lina (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Character recognition is one of the areas of the pattern recognition field that continues to be developed today. Character recognition is a process of recognizing a character independently or based on the similarity with the data that have been there before. Character recognition aimes to allow a system to recognize characters easily and effectively.One method of charater recognition is the Scale-Invariant Feature Transform (SIFT). SIFT is an algorithm that is designed to detect and explain the features of the image, while Mahalanobis Distance and Eulidean Distance is a method used to measure the similarity of an image by measuring the distance between test image and train image. The combined method is designed to achieve high recognition accuracy of a character recognition system.